Comparison of 3D Gradient-Echo Versus 2D Sequences for Assessing Shoulder Joint Image Quality in MRI - Shapoor Shirani; Najmeh-Sadat Mousavi; Milad Ali Talib; Mohammad Ali Bagheri; Elahe Jazayeri Gharebagh; Qasim Abdulsahib Jaafar Hameed; Sadegh Dehghani (International Journal of Biomedical Imaging)
Conclusions: 3D-GRE sequences provide superior image quality and efficiency for evaluating articular joints, particularly in shoulder imaging. The TRUEFISP technique offers the best contrast and signal quality, making it a valuable tool in clinical practice.